Huyang Yangkun formula regulates the mitochondria pathway of ovarian granulosa cell apoptosis through FTO/m6A-P53 pathway - Li, Yang; Wang, Lingdi; Liu, Jian; Nie, Guangning; Yang, Hongyan (Frontiers in Pharmacology, 2024)
Background: Premature ovarian insufficiency (POI) presents a significant challenge to female reproductive health. The Huyang Yangkun Formula (HYF), a traditional Chinese medicinal formulation, has been utilized in clinical settings for the treatment of POI for over a decade. Nevertheless, the therapeutic application of HYF is considerably constrained by the lack of clarity regarding its underlying mechanism of action.The experimental procedures entailed administering VCD to female Sprague-Dawley rats at a dosage of 160 mg/kg/day over a period of 15 days, succeeded by a 100-day treatment with HYF. Blood serum samples were collected and analyzed using ELISA to quantify the concentrations of Anti-Müllerian Hormone (AMH), Follicle-Stimulating Hormone (FSH), and Estradiol (E2). The levels of N6methyladenosine (m6A) were assessed through Dot blot analysis and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Western blotting was employed to validate the differential expression of m6A-related catalytic enzymes and